Pendampingan Wirausaha Start-Up Animasi Berbasis Jasa - Johansen Johansen; Aluisius Hery Pratono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Over the past year, there have been developments in Indonesia’s creative industry, the animation subsector, both in providing services and producing IP independently. Although the animation sector industry researchers are presented with an effective and efficient animation industry model from ideation to distribution, the model is still difficult to use in Indonesia because of existing limitations so that they are still dependent on government funding. Whereas for the last 65 years there is still no real role that has been done by the Indonesian government to help the growth sector of this sector. So this raises the question of what other things can we do as private parties in developing IP by not relying on funding by the government? Animation, especially in IP production, ia a business with enormous prospects for its impact on the recovery, growth, and development of the Indonesian economy. There are author who have thought about methods that can be carried out or used in efforts to manage this sector. In an effort to realize the things that are dreams of creative industry business actors will be briefly discussed through this critical literature review.